The Unfractured Faith of Erik Routley: From Brighton to Princeton - Graham, Nancy L. (Lexington Books, 2023)
Erik Routley, Reformed churchman, musician, and theologian is arguably the most significant hymnologist of the twentieth century. In The Unfractured Faith of Erik Routley: From Brighton to Princeton, Nancy L. Graham unveils Routley’s extraordinary life through his own eyes. Anecdotes from nearly forty years of correspondence with his many colleagues and friends enliven the foundations of Routley’s faith, scholarship, and pastoral relationships until his untimely death in 1982. Congregation members from his churches in Edinburgh and Newcastle, former students, fellow clergy, and editorial partners recall Routley’s energy, wit, and straightforward observations, as well as the riveting effect of his sermons and lectures. Routley’s extensive works explore the prophetic and timeless assertion that musicians and preachers are synergistic artists in service to the Gospel. An important part of this book is the detailed description of the Dunblane Music Consultations that lit the hymn explosion of the 1960s. The effects of these remarkable collaborations rippled through the next generation of writers and composers and are the unsung groundwork for the current approach to hymn writing.